COVID-19 and Student Life: An Ubuntu and resilience perspective on the experiences of African International University Students in the United States - Tefera, Gashaye Melaku; Onyeaka, Kelechi; Conteh, Nameri; David, Ifeolu; Kehinde, Omoshola; Harvey, Idethia; Majee, Wilson (Journal of International Students, 2023)
While COVID-19 affected all segments of the population, vulnerable social groups, including international students, were disproportionately affected. The primary objective of this study was to explore COVID-19-related experiences of African international graduate students (AIGS). Qualitative data were collected through in-depth interviews with 15 AIGS. Interviews were audio-recorded, transcribed verbatim, and thematically analyzed. Participants reported experiencing fear of the virus and anxiety about their health and their family members (individual), feelings of isolation and depression because of reduced social engagement and lack of familial support (interactional), dealing with work restrictive student visas, and loss of work opportunities (environmental/structural). The person-in-environment (PIE) and Ubuntu philosophy were useful lenses to understand the findings in the context of COVID-19 given its socio-cultural connection to AIGS.Understanding the experiences of AIGS can help inform better approaches, including institutional and national policy changes, to support not only AIGS but also vulnerable international students during pandemics.